Menakibname Of Uryan Hizir (Journal of Alevism-Bektashism Studies, 2010)
Uryan Hızır had been worked to spread, together with disciples of Islam who was Abdalan-ı Rum so that he set up in Tunceli county, in Pertek township and Zeve Village a small dervish lodge. After his death Menakıbname was written by to what is narrated Hızır Tac. The information’s life Uryan Hızır in Menakıbnamede, there are also details of Alevi founders lodge and into the realm of the relationship between Alevi lodge. In this article, this information with the modern research menakıbnamede by comparison is tried to analyze.